PEREMPUAN DALAM CAKRAWALA SUFISME, TELAAH MENDALAM ATAS KARYA MUHAMMAD NUR JABIR - Gazali, Hidayatul Azizah; Sefri Auliya (Bahasa Indonesia, 2025)
The reality that develops in society shows that the role of women is often still viewed marginally, both in the social and spiritual domains. Women are frequently reduced to merely biological aspects and domestic roles, without considering their spiritual depth within the Islamic tradition. This study aims to offer a broader and more holistic perspective on women by positioning them as part of the manifestation of Divine beauty, possessing the potential to achieve spiritual perfection. Through the works of Muhammad Nur Jabir, this research seeks to explore how women in Sufism are not only understood as passive objects but also as active subjects in the journey toward God. This research is categorized as a literature study with a qualitative approach. The data analysis method applied is content analysis. The findings of this study indicate that, first, women are seen as the dominant reflection of God’s jamaliyah (beauty) attributes, while men reflect jalaliyah (majesty) attributes; however, these two dimensions complement each other to create spiritual balance. Second, in their essence of creation, women and men are considered spiritually equal as they originate from the same soul, whereas differences in Islamic law are more related to physical aspects. Third, women have the same potential as men to reach the highest spiritual levels, such as the maqam of sainthood (insan kamil) and the maqam of caliphate (khalifah).